(untitled) (Research, Society and Development, 2020)
The aim of this study was to evaluate the effect of inoculant doses and their interactions with biostimulant on common bean. The study was developed in the experimental area of the State University of Mato Grosso do Sul, in Aquidauana-MS, using the cultivar TAA Dama of the commercial group carioca. The experimental design was randomized blocks, in a 2x5 factorial scheme, with four replications. The first factor is the presence or absence of the Stimulate® biostimulant application. The second inoculant dose factor (0 mL, 150 mL, 300 mL, 600 mL, 1200 mL every 50 kg of seeds). They were evaluated the number of nodules per plant, nodular activity, green and dry matter of nodules, green matter and dry matter of shoot and root, root length and density, nitrogen content and leaf phosphorus, height of first pod insertion, height of plants, number of branches, number of, number of grains per pod, mass of one hundred grains and yield. The application of the biostimulant alone or in association with Rhizobium tropici in common bean seeds does not promote increase of grain yield in the culture, as opposed to the practice of inoculation with the rhizobia. The recommended dose of the inoculant based on R. tropici provides increases in the productivity of the common bean. Increasing the dose is just a waste.